Health is wealth : health progrmme - Mackenzie, James; Haldane, William S. ([Scotland : Industrial Health Education Council], 1926)
1926 1926 1920s 16 pages 4 Medical Members of Council. T. ADAM, M.A., M.D., M.R.C.S., L.R.C.P., D.P.H., Secretary of Society of Medical Officers for Scotland. GEO. BANKS, M.B., Ch.B., D.P.H., Aberdeen. H. STANLEY BANKS, M.A., M.B., Ch.B., D.P.H., Motherwell. A. LAURIE BROWN, L.R.C.S., L.R.C.P.E., Glasgow. W.F. BROWN, M.B., C.M., D.P.H., Ayr. JAMES BURNETT, M.A., M.D., F.R.C.P.E., Edinburgh. A.S. CAMPBELL, M.B., Ch.B., L.R.C.P., L.R.C.S., Dundee. A.K. CHALMERS, M.D., C.M., F.R.F.P.S., Glasgow. L. CROMBIE, M.B., Ch.B., Dalmuir. ANDREW GIBSON, M.B., F.R.C.S. (Edin.) Baillieston. H.C. DONALD, M.B., C.M., F.R.C.S., Paisley. Professor JOHN GLAISTER, M.D., D.P.H. (Cam.), F.R.C.P., etc., Regius Professor of Forensic Medicine, University, Glasgow. JOHN GLAISER, Jun., M.B., Ch.B., Glasgow. Professor J.S. HALDANE, M.D., F.R.S., President of Institution of Mining Engineers, and Chairman of Commitees on Hot and Deep Mines (Institute of Mining Engineers), and Miners' Nystagmus (Medical Research Council). R. HAMILTON, M.B., C.M., D.P.H., Coatbridge. P. HOWIE, M.B., C.M., Aberdeen. A.G. HAY, M.D., Glasgow. A.E. KIDD, O.B.E., M.B., C.M., Dundee. J. PARLANE KINLOCH, M.D., Ch.B., D.P.H., Aberdeen. J. LIVINGSTONE LOUDEN, M.D., C.M., D.P.H., Hamilton. A.S.M. MACGREGOR, M.D., D.P.H., Glasgow. CHRISTINA A. MAYNE, M.B., Ch.B., Edinburgh. MARGARET R. MARTIN, M.B., Ch.B., Edinburgh. WM. M'ALLISTER, M.D., Kilmarnock. WM. M'EWAN, M.D., Prestonpans. G.W. M'Intosh, M.D., C.M., B.Sc. (P.H.), Kirkcaldy. DAVID M'Kail, M.D., Glasgow. G.V.. M'Michael, M.B., Ch.B., Paisle. Sir THOMAS OLIVER, M.D., LL.D., D.Sc., F.R.C.P., Newcasle-upon-Tyne, Author of "Diseases of Occupations." EDWARD J. PRIMROSE, M.D., M.B., C.M., F.R.F.P.S., Glasgow. T. THOMSON PRANGNELL, M.D., C.M., D.P.H., Falkirk. ALEX. ROBB, M.A., M.D., C.M., Edinburgh. WM. ROBERTSON, M.D., D.P.H., F.R.C.P., Edinburgh. MARGARET SCOTT DICKSON, M.B., Ch.B., Dundee. ALEX. SCOTT, M.D., Broxburn. LAURA STEWART-SANDEMAN, M.D., M.B., Ch.B., Aberdeen. Mrs. EDITH SHANNON, M.B., Ch.B., Glasgow. T. LAUDER THOMSON, M.D., Ch.B., Dumbarton. DOROTHY A. TOWART, M.B., Ch.B., Glasgow. J.H. GARCIA WHITEFORD, B.A., M.B., Greenock. G. PRATT YULE, M.D., C.M., B.Sc. (P.H.), F.R.C.P., Cupar-Fife. With the co-operation of the Society of Medical Officers of Health for Scotland. 200/B/3/2/C693/1/48